2020
DOI: 10.1177/0956797620904450
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Adopted and Nonadopted Individuals Reveals Gene–Environment Interplay for Education in the UK Biobank

Abstract: Polygenic scores now explain approximately 10% of the variation in educational attainment. However, they capture not only genetic propensity but also information about the family environment. This is because of passive gene–environment correlation, whereby the correlation between offspring and parent genotypes results in an association between offspring genotypes and the rearing environment. We measured passive gene–environment correlation using information on 6,311 adoptees in the UK Biobank. Adoptees’ genoty… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(100 citation statements)
references
References 40 publications
4
94
1
1
Order By: Relevance
“…Secondly, indirect genetic effects can be estimated by comparing polygenic score associations estimated in a sample of adoptees against those estimated for individuals who were reared by their biological parents (Cheesman et al 2020). Therefore, we estimate the regression model shown in Equation 2 separately for adoptees and for non-adopted individuals.…”
Section: Three Designs For Estimating Direct and Indirect Polygenic Smentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, indirect genetic effects can be estimated by comparing polygenic score associations estimated in a sample of adoptees against those estimated for individuals who were reared by their biological parents (Cheesman et al 2020). Therefore, we estimate the regression model shown in Equation 2 separately for adoptees and for non-adopted individuals.…”
Section: Three Designs For Estimating Direct and Indirect Polygenic Smentioning
confidence: 99%
“…They denote the effects of numerous heritable parent characteristics, without the need for measures of specific parent phenotypes. Complementary evidence of indirect effects of parents' educationlinked genetics on offspring education has also accumulated from sibling and adoption designs, depicted in Figure 1 (Kong et al 2018;Bates et al 2018;Selzam et al 2019;Cheesman et al 2020). Although no research has systematically compared estimates of indirect genetic effects across cohorts, they generally are 30-50% the magnitude of direct genetic effects in these studies.…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence from family-based studies suggested that a substantial fraction of genetic associations may be mediated by the family environment [6][7][8][9][10][11][12][13][14][15][16] . In particular, parental genotypes could affect the family environment through the parents' educational attainment 17 , personalities 18,19 , behavior [20][21][22][23][24] , and socioeconomic status 25 , which could subsequently affect the offspring's phenotypes 26 .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Black people in the US, for reasons unrelated to genetics, live in areas with poorer air quality and more exposure to environmental toxins 39 . Polygenic scores are also known to be biased by the non-random ways that people choose their spouse/partner (assortative mating 40 ); the ways that genes interact with different environments (gene-environment interaction [41][42][43] ); or 7 160 165 170 175 180 differences in genetic features that genome-wide association studies rely on, which create the illusion of systematic differences between African and non-African populations (linkage disequilibrium, genetic drift, epistasis and ascertainment bias 32,44,45 ). These kinds of biases have previously led to improper inference of natural selection in even closely related European populations 46,47 .…”
Section: Application Of Polygenic Scores To Group Differencesmentioning
confidence: 99%
“…Indirect genetic effects, however, are often more amenable to environmental interventions 82 . This is bolstered by the observation that much of the effect size disparity between within-and between-family polygenic scores of 21 480 485 490 495 500 cognitive traits is related to socioeconomic status, which can be changed readily through social policies 40,41 . Should proponents of the genetic hypothesis argue that indirect genetic effects nonetheless support their claims, such a premise would be inconsistent with maintaining any claims of the fixedness of the phenotypic gap, which is a centerpiece of arguments made by Jensen 8,9 ,Rushton 83 , and Lynn 7 .…”
Section: No Evidence Of Divergent Natural Selection Between Africansmentioning
confidence: 99%